Penambahan Fraksi Pasir dan Amelioran terhadap Sifat Fisika dan Kimia Tanah Salin yang Sudah Dilindi - Arif Rahman; Ismed Fachruzi; Muhammad Syarbini (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2024)
Several problems arise so that saline soil is rarely used for plant cultivation, including: (1) low organic C in saline soil, (2) low N and K elements, (3) high pH, ​​(4) high Na+ content and (5) high plant osmotic pressure. This research aims to determine the effect of adding sand, applying processed organic fertilizer from fishery waste, and chicken manure on improving several physical and chemical properties of saline soil. This research used a factorial Completely Randomized Design (CRD) with two factors. Where factor A consists of: A1 = additional sand 25% of 1 kg soil weight (250 g); A2 = 35% additional sand from 1 kg of soil weight (350 g) and factor B consists of: B1 = Organic fertilizer from fishery waste is increased to 5% of 1 kg of soil weight (50 g); B2 = Chicken manure is increased to 5% of 1 kg of soil weight (50 g). Results show that the combination of adding 350 g of sand and applying chicken manure showed the best results for leaching dissolved salts and increasing soil pH.